2015
DOI: 10.1007/s11368-015-1061-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen deposition rates and frequencies on the abundance of soil nitrogen-related functional genes in temperate grassland of northern China

Abstract: Purpose Microbial processes driving nitrogen (N) cycling are hot topics in terms of increasing N deposition. Abundances of N-related functional genes (NFG) can be most responsive to N deposition and commonly used to represent N transformation rates. However, empirically simulated N deposition has been exclusively conducted through large and infrequent N fertilization, which may have caused contrasting effects on NFGs.Therefore, experiments with small and frequent N additions closed to natural deposition are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 68 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…The strong dominance of ammonia-oxidizing thaumarchaeota within the archaeal communities was further supported by the numerical predominance of archaeal amoA gene abundances (~5 × 10 7 copies g −1 soil) relative to bacterial amoA gene abundances (mostly ≤ 7 × 10 4 copies g −1 soil). To our knowledge, a predominance of archaea within the ammonia-oxidizing communities has not yet been described for savanna soils but is well known for various other soil environments (e.g., Erguder et al, 2009 ; Herrmann et al, 2012 ; Sims et al, 2012 ; Ding et al, 2015 ; Ning et al, 2015 ). AOA tend to dominate over AOB in acidic soils and can also thrive at much lower substrate concentrations than AOB due to a higher substrate affinity (Leininger et al, 2006 ; Martens-Habbena et al, 2009 ; Zhang et al, 2012 ; Yao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 90%
“…The strong dominance of ammonia-oxidizing thaumarchaeota within the archaeal communities was further supported by the numerical predominance of archaeal amoA gene abundances (~5 × 10 7 copies g −1 soil) relative to bacterial amoA gene abundances (mostly ≤ 7 × 10 4 copies g −1 soil). To our knowledge, a predominance of archaea within the ammonia-oxidizing communities has not yet been described for savanna soils but is well known for various other soil environments (e.g., Erguder et al, 2009 ; Herrmann et al, 2012 ; Sims et al, 2012 ; Ding et al, 2015 ; Ning et al, 2015 ). AOA tend to dominate over AOB in acidic soils and can also thrive at much lower substrate concentrations than AOB due to a higher substrate affinity (Leininger et al, 2006 ; Martens-Habbena et al, 2009 ; Zhang et al, 2012 ; Yao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 90%
“…Many studies have found that N addition increases the richness of diazotrophs 33 , 34 . However, some studies have found that N has no such clear influence 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this difference may be that (1) the original N content in the rocky soil and the level of urea applied to the rocky soil were very low, as in the Antarctic soils and semiarid grassland (Jung et al, 2011;Zhang et al, 2019). A previous study also found that nifH gene abundance increased under low N rates (5-15 g N/m 2 /year) but was suppressed under high N rates (50 g N/m 2 /year) (Ning et al, 2015). It was suggested that low N fertilization (0.7 g N/m 2 ) may have promoted the growth of N-fixing microorganisms in the N-deficient soil.…”
Section: Microorganism Community Improved Rocky Soil Qualitymentioning
confidence: 99%